Some characterizations of Asian elephant (Elephas maximus) semen alpha-L-fucosidases - Paewponsong, Kamonchanok; Khunsook, Sumpars (Asia-Pacific Journal of Science and Technology, 2021)
Alpha-L-fucosidase is an enzyme found in several organisms. Commonly, its function is the degradation of L-fucose containing biomolecules in lysosomes. Moreover, the enzyme is also found in sperm and seminal plasma. It plays an important role in sperm-egg binding. In this study, sperm and seminal plasma alpha-L-fucosidases of Asian elephants were characterized for the first time. The results showed that the average volume of semen was 27 mL, the pH was 7, the sperm motility was 20-50%, and the average concentration was 539 × 106 cells/mL. The localization of alpha-L-fucosidase was determined by the immunoperoxidase technique. The results revealed that the enzyme is localized at the plasma membrane of the sperm over the head and tail regions. Western blot results of the seminal plasma alpha-L-fucosidase showed three bands of 50.7, 24.3 and 12.6 kDa, whereas those of the sperm showed a band of 40 kDa. The optimal pH of seminal plasma alpha-L-fucosidase ranged between 3.2-6.6 with over 80% of maximal activity. Similarly, over 80% of the enzyme activity in sperm were found with a broad range of pH (3.4-6.6). Several isoforms of seminal plasma alpha-L-fucosidase were revealed by isoelectric focusing, including two major isoforms (pI 7.48, 7.98) and four minor isoforms (pI 3.33, 5.19, 8.43 and 8.80). This work reveals the presence of alpha-L-fucosidases in Asian elephant semen and helps us to better understand its properties, as well as providing information that may be useful in the development of reproductive biotechnology for breeding and the conservation of this endangered species.